Effect of gender on blood flow velocities and blood pressure: role of body weight and height - Noor Azmi, Azran Azhim; Akioka, Kohei; Akutagawa, Masatake; Hirao, Yuji; Yoshizaki, Kazuo; Obara, Shigeru; Nomura, Masaharu; Tanaka, Hiroyuki; Yamaguchi, Hisao; Kinouchi, Yohsuke (IEEE, 2007)
Aging and gender alter arterial hemodynamic function. Gender-related differences in body size may affect the arterial hemodynamics such as systolic blood pressure, wave reflection and pressure wave propagation. To assess the possibility that the differences of carotid blood velocities and brachial blood pressure in women are related to body size, we investigated the arterial hemodynamics in 50 healthy young adults (30 men, 20 women) between the age ranges of 20 to 29 years old. Blood velocities are characterized to 5 components of velocity waveforms as peak systolic (S1), second systolic (S2), incisura between systole and diastole (I), peak diastolic (D) and end-diastolic velocity wave (d). As the most pronounced systolic blood pressure is lower in young women than men (P<0.05). Women have higher diastolic velocity components and second systolic velocity, but have lower systolic velocity compared to men. From that, women have a significant greater wave reflection, smaller vascular resistive and lower vascular elastic recoil than in men. Greater body weight is associated with higher blood pressures (P<0.05) and lower blood velocities (P<0.05). Shorter body height affects not only the increased velocity wave reflection index (r= -0.519, P>0.0001), but also the decrease of peripheral vascular resistive index (RI) and arterial vascular elastic recoil index (r= 0.463, P<0.0001; r= 0.481, P<0.0001, respectively). In conclusion, body size influences blood pressure and velocity regulations in the young population.